FORSKOLIN: ITS THERAPEUTIC APPLICATIONS - KAUSHIK PURANAM; SUREKHA RANI.H (International Journal of Pharma and Bio Sciences, 2014)
Medicinal herbs are moving from fringe to mainstream use with a greater number of people seeking remedies.Forskolin, is a diterpene, the main active ingredient in the ayurvedic herb Coleus forskohliihas been used in India since prehistoric times in ayurvedic traditional medicine.Coleus forskohliiis a perennial aromatic herb found in subtropical regions of India, Nepal and Srilanka.Forskolin activates the enzyme adenylatecyclase, results in increased cAMP in cells. Cyclic AMP is involved in several biological processes, including inhibition of platelet activation, reduced release of histamine, increased force of contraction of the heart, relaxation of the arteries and other smooth muscles, and increased lipolysis and also cures various diseases like asthma, eczema, psoriasis, angina, obesity,hypertension, glaucoma,acts as antimetastatic and protect cells from UV induced damage, ageing of skin. Studies are warranted to understand the effect of forskolin on various diseases for its utility in therapeutics.